Effects of Health Counseling on Mother's Knowledge Level in Pumping Implementation - Haerani; Muriyati; Merni (Jurnal Life Birth, 2019)
The method of pumping ASI (pumping) is one of the fastest and most efficient methods to increase the production of breast milk (ASI), in addition, it will provide comfort to the mother and the confidence to continue to breastfeed is also increasing. Based on the results of an initial survey conducted by researchers in the Moti Puskesmas Work Area, it was found that several mothers did not know about pumping, and did not know about the method of implementing pumping. Knowing the effect of providing health education to the level of knowledge of mothers about the implementation of pumping in the working area of ​​Moti Health Center, Gantarangkeke District, Bantaeng Regency. This type of research is quantitative research, this type of research uses quasi-experimental research with a non-randomized pretest-posttest with control group design. The research sample of 30 respondents. Taken by consecutive sampling method. Data analysis in this study used the Wilcoxon test statistic test. Based on the results of the analysis of differences in the level of maternal knowledge about the implementation of pumping before and after the provision of health education in group 1 (Flipchart), the significance value was 0.008 (p <0.05). While based on the results of the analysis of the level of maternal knowledge about the implementation of pumping before and after the provision of health counseling in group 2 (Leaflets) obtained a significance value of 0,000 (p <0.05). There is an effect of providing health education to the level of knowledge of mothers about the implementation of pumping in the working area of ​​Moti Health Center, Gantarangkeke District, Bantaeng Regency.